The Early Impact of the COVID-19 Lockdown on Stress and Addictive Behaviors in an Alcohol-Consuming Student Population in France - Flaudias, Valentín (2021)
This study evaluated factors linked with perceived stress related to the COVID-19 pandemic and lockdown and addictive behaviors prior to and during lockdown in a sample of students who indicated engaging in alcohol consumption behaviors before lockdown. Methods: Cross-sectional study. French students from four universities participated in this study, and 2,760 students reported alcohol use. During the first week of lockdown, students reported their perceived levels of stress regarding COVID-19. Substance use and addictive behaviors were reported before and during lockdown, and media exposure, demographical, living conditions, and environmental stressors were reported during lockdown. Results: Women reported greater levels of stress (95% CI: 1.18 to 1.93, p < 0.001). Highly-stressed students also report less social support (95% CI: -1.04 to -0.39, p < 0.001) and were more likely to worry about the lockdown (95% CI: 0.27 to -0.65, p < 0.001). Alcohol-related problemswere more prevalent among the most stressed students (95% CI: 0.02 to 0.09, p = 0.004) as well as eating problems (95% CI: 0.04 to 0.36, p = 0.016) and problematic internet use (95% CI, 0.06 to 0.14, p < 0.001). Students reporting the highest levels of stress also indicated more compulsive eating during the previous seven days (95% CI, 0.21 to 1.19, p = 0.005). Conclusions: The level of stress was strongly related to four categories of variables: (i) intrinsic characteristics, (ii) addictive behaviors before lockdown, (iii) lockdown-specific conditions, and (iv) addictive behaviors during the lockdown. Several variables linked to COVID-19 were not directly linked with perceived stress, while perceived stress was found to correlate with daily life organization-related uncertainty and anticipated consequences of lockdown. Importantly, social support seems to be a protective factor on high level of stress.